2002
DOI: 10.1097/01.mp.0000036347.66943.3c
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Four Distinct Regions of Allelic Imbalances on Chromosome 1 by the Combined Comparative Genomic Hybridization and Microsatellite Analysis on Hepatocellular Carcinoma

Abstract: Frequent chromosome 1 abnormalities detected in human hepatocellular carcinoma have been implicated in early genetic events of liver carcinogenesis. Recurrent loss of 1p with a common deleted region 1p36 -p34 has been reported from microsatellite analysis, whereas common gain of the whole chromosome q-arm was described from several comparative genomic hybridization studies. The relationships between copy number changes and allelic status however remains unclear. In this study, we have conducted a simultaneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…Positional mapping of typical HCC has further narrowed the regions of interest for the 1q oncogene:1q21-q22 [14], 1q23.1-q24.2 [5], 1q32.1 [5], and 1q43-q44 [5]. Our findings further point to the region of chromosome 1q23.1 as the likely critical region containing an important oncogene.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Positional mapping of typical HCC has further narrowed the regions of interest for the 1q oncogene:1q21-q22 [14], 1q23.1-q24.2 [5], 1q32.1 [5], and 1q43-q44 [5]. Our findings further point to the region of chromosome 1q23.1 as the likely critical region containing an important oncogene.…”
Section: Discussionmentioning
confidence: 64%
“…This chromosome 1q region is also frequently gained in typical HCC and is widely thought to contain an oncogene(s). Additional studies of typical HCC have further narrowed down the likely regions that contain an oncogene to include 1q21-23 and 1q42 [5].…”
Section: Introductionmentioning
confidence: 98%
“…In this study, it is found that the phenotyping was obviously distinct from LOH in 19.6% (11/56) of all cases examined, identified when greater difference is seen in the relative allele intensity ratio between the tumor DNA and normal DNA. This phenomenon was recently reported and much less is known about its significance [22] . It is not known that an unique instability phenotyping or a sub-type of LOH and MSI, but additional studies are needed.…”
Section: Discussionmentioning
confidence: 97%
“…Using differential display analysis of gene expression profile of hepatocelllular carcinoma (HCC), we found frequent overexpression of ASPM, which is located at chromosome 1q31, a region with frequent gain in HCC (25,26). In this study, we showed that ASPM was often overexpressed in human HCC and associated with tumor progression, early tumor recurrence (ETR), and poor prognosis.…”
mentioning
confidence: 78%